Pengaruh Pijat Perineum terhadap Rupture Perineum di Wilayah Binaan Puskesmas Megang Kota Lubuklinggau Tahun 2025 - Dela Putri Amand; Diyah Tepi Rahmawati; Febra Ayudiah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Perineal rupture is one of the leading causes of maternal mortality. (Indonesian Ministry of Health, 2024) The provinces with the highest incidence of perineal rupture are West Java (54%), East Java (39%), East Nusa Tenggara (9%), and South Sumatra (7.8%). The incidence of perineal rupture recorded in Lubuk Linggau City is 7.3% (South Sumatra Provincial Health Office, 2024). Based on data from the Megang Community Health Center in Lubuklinggau City from January to September 2025, out of 203 individuals, 87 (42.8%) experienced perineal rupture. The objective of this study was to determine the effect of perineal massage on perineal rupture. The Quasi-Experimental Design (Quasi-Experimental Design) was employed using a Two-Group Pre-Test-Post-Test design; data were collected through observation of 15 respondents who received perineal massage and 15 who did not, using total sampling. The results of the univariate analysis showed that the degree of perineal rupture in the intervention group of 15 respondents was mostly Grade 1 in 8 (53.3%) of the respondents. The degree of perineal rupture in the intervention group of 15 respondents was Grade 1 in 7 (46.7%) of the respondents and Grade 2 in 7 (46.7%) of the respondents. Results of the bivariate analysis showed that there was an effect of perineal massage on the intervention and control groups in the Megang Health Center Service Area, Lubuklinggau City, in 2025, with a significance value of p = 0.009 < 0.05. The researchers suggest that perineal massage be integrated into public health practices. The results of the univariate analysis showed that among the 15 respondents in the intervention group, the majority (8 respondents, or 53.3%) had a perineal rupture of grade 1. Among the 15 respondents in the intervention group, nearly half (7 respondents, or 46.7%) had a perineal rupture of grade 1, and 7 respondents (46.7%) had a perineal rupture of grade 2. Results of the bivariate analysis showed that there was an effect of perineal rupture in the intervention and control groups in the Megang Community Health Center catchment area, Lubuklinggau City, in 2025, with a significance value of p = 0.009 < 0.05. The researchers suggest that perineal massage be integrated into educational activities for pregnant women as a strategy to reduce the incidence of perineal trauma and improve the quality of maternal and child health services in the community